Drift resonance and particle removal from helical plasma - Antufyev, O.; Pavlenko, I.; Girka, I. (Вопросы атомной науки и техники, 2015)
The effect of magnetic field perturbation on motion of deuterium, tritium and helium ions is studied theoretically and by numerical simulation of the charged particle motion in electromagnetic field. A method for alpha-particles (fusion reaction product) removal from plasma in helical device due to drift resonance formation is proposed. The point is that helium ion escapes from the confinement volume due to the natural drift in inhomogeneous magnetic field. Теоретически и с помощью численного моделирования движения заряженных частиц в электромагнитном поле изучено влияние возмущения магнитного поля на движение ионов дейтерия, трития и гелия. Предложен метод удаления альфа-частиц (продуктов реакции синтеза) из плазмы винтовой ловушки с помощью формирования дрейфового острова. Основной особенностью является то, что ион гелия уходит из объёма удержания благодаря естественному дрейфу в неоднородном магнитном поле. Теоретично та за допомогою числового моделювання руху заряджених частинок в електромагнітному полі вивчено вплив збурення магнітного поля на рух іонів дейтерію, тритію та гелію. Запропоновано метод видалення альфа-частинок (продуктів реакції синтезу) з плазми гвинтового пристрою за допомогою формування дрейфового острова. Головною особливістю є те, що іон гелію виходить з об’єму утримання завдяки природньому дрейфу в неоднорідному магнітному полі.